Drastic decline in sera neutralization against SARS-CoV-2 Omicron variant in Wuhan COVID-19 convalescents. Issue 1 (31st December 2022) - Ma, Chengbao; Chen, Xianying; Mei, Fanghua; Xiong, Qing; Liu, Qianyun; Dong, Lianghui; Liu, Chen; Zou, Wenjing; Zhan, Faxian; Hu, Bing; Liu, Yingle; Liu, Fang; et al.
ABSTRACT: Global concern has been raised by the emergence and rapid transmission of the heavily mutated SARS-CoV-2 Omicron variant (B.1.1.529). So far, the infection features and immune escape ability of the Omicron variant have not been extensively studied. Here, we produced the Omicron pseudovirus and compared its entry, membrane fusion, and immune escape efficiency with the original strain and the dominating Delta variant. We found the Omicron variant showed slightly higher infectivity than the Delta variant and a similar ability to compete with the Delta variant in using Angiotensin-converting enzyme 2 (ACE2) in a BHK21-ACE2 cell line. However, the Omicron showed a significantly reduced fusogenicity than the original strain and the Delta variant in both BHK21-ACE2 and Vero-E6 cells. The neutralization assay testing the Wuhan convalescents' sera one-year post-infection showed a more dramatic reduction (10.15 fold) of neutralization against the Omicron variant than the Delta variant (1.79 fold) compared with the original strain with D614G. Notably, immune-boosting through three vaccine shots significantly improved the convalescents' immunity against the Omicron variants. Our results reveal a reduced fusogenicity and a striking immune escape ability of the Omicron variant, highlighting the importance of booster shots against the challenge of the SARS-CoV-2 antigenic drift.